The New Testament speaks ; v. 4 explaining the New Testament as it was understood by its first readers - Fleming, Donald C. (Manila, Philippines Living Books for All, 1976)
Contents : v. 4 : Galatians - Philemon.
Brethren writer. Donated by the author.
Keywords: Bible. N.T. -- introductions